Making sense of global warming: Designing a human resource development response. Issue 5 (2014) - ,
Abstract : Purpose – This study aims to make sense of global warming. Using the concept of design science (as distinct from explanatory science) and by drawing on recent debates in management and organization studies, the study considers whether the principal mission of human resource development (HRD) research should be to design and develop actionable knowledge that practitioners in organizations can use to solve their pressing field problems. By way of illustration, it poses the question of whether HRD research, in terms of design science principles, can offer solutions to one of the most pressing problems confronting humanity, i.e. global warming.Design/methodology/approach – The study does this from the perspective of dual process theories of human cognition in discussing the arguments presented by various researchers that experiential/intuitive modes of sensemaking are more likely to mobilize effective pro‐environmental behaviours than are the traditional rational/analytical modes of sensemaking employed in many HRD and educational interventions and programmes.Findings – An inference that may be drawn is that HRD research may be better positioned not as an academic discipline nor as subordinate or superordinate to human resource management, but rather as an emergent solution‐oriented "design science".Originality/value – The study uses design science perspective for HRD. Acknowledgements : This article is based on a paper presentation to the University Forum for Human Resource Development (UFHRD) Conference, University of Brighton, 5‐7 June 2013.